Relationship between the provision of complementary foods and the nutritional status of infants aged 6-11 months - Reza, Yulinda; Fatonah, Oon; Rosita, Desy (ELECTRON (Journal of Science and Technology), 2024)
Malnutrition contributes to morbidity, mortality, disability, and reduced national human resource quality. Adequate nutrition during infancy is essential for optimal growth, with exclusive breastfeeding recommended for the first six months and continued breastfeeding with nutritious complementary foods thereafter. In 2017, exclusive breastfeeding coverage in Mempawah District was only 60.7%, and the Wajok Hulu Community Health Center had the lowest rate at 24.1%, indicating many infants received complementary foods too early. This study aimed to examine the relationship between complementary feeding and the nutritional status of infants aged 6–11 months in Wajok Hulu Village. Using a retrospective case–control design with 64 infants, results showed that most infants had good nutritional status despite receiving inappropriate complementary feeding. The study concluded that there was no significant relationship between complementary feeding practices and nutritional status (p = 0.337), suggesting that other factors may play a greater role in determining infant nutrition.